Tinjauan literatur sistematis digitalisasi koleksi antikuariat di perpustakaan khusus - Ersya Julia Hermadilla; Tamara Adriani Salim (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. From a rare collection preservation perspective, antiquarian collections are considered fragile and prone in terms of biological, chemical and physical damage. This causes antiquarian collections require special handling to preserve. Data Collection Methods. This study used a systematic literature review with a qualitative approach using Google Scholar. Based on the searching process, we analysed three articles. Data Analysis. The data was obtained and analysed by describing the content of the articles, including the ideas of problem solving and recommendations in the articles. Results and Discussion. The digitisation of antiquarian collections aims to improve user services by providing access to digital antiquarian collections and to preserve them. There are three main activities in the process of digitising antiquarian collections, namely selecting, scanning and storing. Conclusion. This study provides an overview of the digitisation process of antiquarian collections conducted by special libraries. More particularly, the special libraries must manage sufficient budget and plan to conduct the digitisation process of antiquarian collections.